International conference machinery, electronics and control simulation : selected, peer reviewed papers from the International Conference Machinery, Electronics and Control Simulation (ICMECS 2014), September 27-28, 2014, Weihai, Shandong Province, China - Wang, Li (Applied mechanics and materials, 2014)
Collection of selected, peer reviewed papers from the the International Conference on Machinery, Electronics and Control Simulation (ICMECS 2014), September 27-28, 2014, Weihai, Shandong Province, China. The 146 papers are grouped as follows: Chapter 1: Dynamics and Mechanical Engineering, Applied Mechanics, Chapter 2: Materials Engineering and Processing, Chapter 3: Mine Engineering, Flow and Ventilation, Thermal Transfer and Effects, Chapter 4: Power and Electrical Engineering, Chapter 5: Control Systems, Mechatronics and Robotics, Chapter 6: Electronics, Embedded and Integrated Circuits, Smart Grid Technologies, Chapter 7: Measurements, Testing, Tracking, Detection and Monitoring, Evaluation, Chapter 8: Signal, Noise, Image Processing, Computational Mathematics and Methods, Chapter 9: Communication, Networks and Information Technologies, Chapter 10: Product Design, Manufacturing and Industrial Engineering, Chapter 11: Civil Engineering and Geoengineering, Chapter 12: Earth Science and Cosmology, Environmental Engineering Keyword: Dynamics and Mechanical Engineering, Applied MechanicsMaterials Engineering and Processing, Mine Engineering, Flow and Ventilation, Thermal Transfer and Effects, Power and Electrical Engineering, Control Systems, Mechatronics and Robotics, Electronics, Embedded and Integrated Circuits, Smart Grid Technologies, Measurements, Testing, Tracking, Detection and Monitoring, Evaluation, Signal, Noise, Image Processing, Computational Mathematics and Methods.